IRED - New initiatives and networks for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
IRED (Innovations et Reseaux pour le Developpement) is an international network of more than 1000 partners in Africa, Latin America and Asia, who mainly belong to associations of small farmers, pastoralists, those working in small-scale crafts and...